Kapasitas Perempuan dalam Pengambilan Keputusan (Suatu Potret Perempuan dalam Birokrasi Pemda Propinsi DIY Terkini) - Syakdiah Syakdiah (Magister Administrasi Publik, 2006)
A large of the population of women 50,3% from total population is resources of development very potential, regulations of legislation nothing different between man and women in government sector, role and position to women still long distance with man community, from total of civil servant and in time his proportion is 60% to man and 40% to women. In local government of province special administrative territory Yogya, his proportion 66,2% to man and 33,8% to women. Women as decision maker and policy formulation in local government of province special administrative territory Yogya still very little, echelon II now 1 people, until need to increased role and position women civil servant pass through education although education of structure, education of gradation and etc education, and need to give a chance bigger again to women civil servant to sit on necessary and have high control toward process of decision of decision maker although policy formulation.